The Dynamics of Productivity and Technical Efficiency Cassava Farming in Trenggalek Regency - Muhammad Haqqi Andika; Sri Widayanti; Ida Syamsu (Universitas Muhammadiyah Jakarta, 2025)
Trenggalek Regency has a relatively large harvested area of cassava in East Java; however, the resulting production is quite low. This issue poses a significant concern. This study aims to determine the level of technical efficiency in cassava farming in Trenggalek Regency as well as examine the dynamics of productivity in the coming years, specifically whether it will increase or decrease. The study employs stochastic frontier analysis and productivity trend analysis. The results show that the average technical efficiency level of cassava farming in Trenggalek Regency is 0.98, indicating that 98% of farmers are already technically efficient. However, the predicted productivity dynamics show a decline of 12.291 quintals/ha per year, with projected productivity in 2024 at 181.10 quintals/ha and in 2025 at 168.81 quintals/ha. Despite the observed technical efficiency in cassava farming from this study, we anticipate a decline in both productivity and technical efficiency among farmers in the years to come